The rouanet law: funding cultural projects or a creative industry in Brazil? - Dowlatyari, Marie (2017)
The purpose of this work is to explore the way the Rouanet Law has been applied in Brazil by addressing participants’ meanings on it and its use to explain why some manage and others fail, as well as their fundraising strategy; finally, this study proposes a series of recommendations to improve the situation of culture financing in Brazil. This paper adopts a qualitative methodology, starting by presenting the Rouanet Law in the text, before exploring current literature on the topic and key findings: general market information from the Ministry of Culture and case studies using the Simbiose Social database and a series of semi-structured interviews of projects and sponsors. The main limitation in writing this work has been the genuinely rare answers obtained [from sponsors who invest money via the Rouanet Law] for interviews. Existing literature on the Rouanet Law deeply lacks micro-data, in particular case studies and interviews. This is what this work offers to do, as well as addressing participants’ meanings on their experiences with the Rouanet Law. In this article, we expect to find and specify the deep differences in the way small social impact projects find funding as opposed to big projects of the creative industry.